2011
DOI: 10.1002/jcp.22538
|View full text |Cite
|
Sign up to set email alerts
|

Role of bone marrow‐derived progenitor cells in the maintenance and regeneration of dental mesenchymal tissues

Abstract: While dental mesenchymal stem cells are well-studied, the origin of these cells is still unclear. Bone marrow-derived cells (BMDCs) have the potential to engraft into several tissues after injury, but whether they can become dental tissue-specific progenitor cells under normal conditions and the relationship of these cells to the tissue-resident cells are unknown. Thus, we transplanted green fluorescent protein (GFP)-labeled BMDCs into irradiated wild-type mice. We found that the engraftment of BMDCs participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 40 publications
0
56
0
Order By: Relevance
“…All procedures of cell culture and identification, of both humans and minipigs, were the same as the previous description71252.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All procedures of cell culture and identification, of both humans and minipigs, were the same as the previous description71252.…”
Section: Methodsmentioning
confidence: 99%
“…However, the periodontium, a complex composed of periodontal ligament (PDL), cementum, alveolar bone and gingiva, is difficult to regenerate integrally. Periodontal ligament stem cells (PDLSCs) and iliac bone-derived MSCs (IBMSCs) were reported to participate in periodontium tissue regeneration10111213, and their interaction also facilitated this process14. Our previous study proved that compound cell aggregates (CAs) of PDLSCs and bone marrow MSCs promoted periodontium regeneration with regenerative microenvironment reconstruction15.…”
mentioning
confidence: 99%
“…For the first question, a recent report may shed some light on the possibility. Zhou et al (2011) utilized BMMSCs from GFP (green fluorescent protein) transgenic mice and transfused them via intravenous injection into irradiated wild-type mice. They found that these transplanted GFP + BMMSCs migrated to and resided in pulp and periodontal ligament.…”
Section: Cell Homingmentioning
confidence: 99%
“…9 hMSCs are promising key candidates for periodontal regeneration purposes. 5,7,20,21 Thus, our study has investigated for the first time the interplay of hMSCs with different oral cell types by means of an innovative in vitro approach, based on interactive cocultures facilitating physiologically relevant nondirect contact-based cell-to-cell interactions, also occurring in vivo.…”
mentioning
confidence: 99%